Albumin inhibits platelet-activating factor (PAF)-induced responses in platelets and macrophages: implications for the biologically active form of PAF. - Grigoriadis, G. (1992)
1. Platelet-activating factor (PAF) binds with high affinity to albumin leading Clay et al. (1990) to suggest that the active form of PAF is the albumin-PAF complex. 2. In the present study the proposal that albumin-bound, rather than monomeric PAF, is the active form of PAF at PAF receptors was critically evaluated by examining the effect of albumin on the potency of PAF in isolated platelets and macrophages. 3. Bovine serum albumin inhibited concentration-dependently PAF-induced responses in platelets and macrophages. The most probable explanation of this finding is that BSA reduced the concentration of free PAF. 4. Thus, we conclude that free PAF, rather than the albumin-PAF complex is the active form. Consequently, local concentrations of albumin will influence profoundly the potency of endogenously released PAF. Moreover, estimates of the affinity of PAF for PAF receptors made in buffers containing BSA, underestimate the true affinity of PAF for its receptors by approximately 3 orders of magnitude.